Peran Ulama sebagai Pengawal Pendidikan Agama Islam di Era Globalisasi - Fauziah, Fauziah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2019)
Ulama essentially have a role in continuing the struggle of the mission of the Prophet Muhammad Saw as he was told that the Ulama were the heirs of the Prophets. Based on this, in forming and maintaining the integrity of Islamic teachings, the role of ulama is very important to place it as a central figure in Islamic religious life. Moreover the understanding of da'wah is related to education, so Islamic religious education is also a very important area in maintaining the values contained in it. In the era of globalization, maintaining the noble values of Islam cannot be done carefully by positioning the ulama as key figures in Islamic da'wah while maintaining the prevailing ethics and norms. The embedding of ulama as a guardian of the Islamic religious education movement cannot be refuted especially in maintaining the morality of the community in participating in building education in Indonesia. In the realm of education, central figures have the power to build a positive culture and maintain a harmonious life.